The Icon of the Twelve Apostles of the Pushkin Museum. Unknown Aspects of a Well–Known Work of Art - Kostić, Elena T. (Actual Problems of Theory and History of Art, 2023)
Despite being underutilized in science, epigraphic heritage, as an integral part of objects of art, worship, and everyday use, is in fact an extremely rich, useful and reliable source of information, not only about the objects themselves, but also about the artists who created them. As an integral part of any inscription, even those which are official or public in character, the graphic idiom contains unique information about the identity of each creator. These elements are effectively identified through forensic analysis, just as in court cases.This essay, using the epigraphic evidence, discusses the identity of the painter of the icon of the Synaxis of the Twelve Apostles from the Pushkin Museum in Moscow. He is recognized as a member of the group of painters who decorated the Church of the Holy Apostles in Thessaloniki, who in fact contributed to the fresco and mosaic decoration of the church. At the same time, the icon is disconnected from the painted decoration of the Monastery of Chora and Panagia Pammakaristos in Constantinople, with which it had been associated in the past. The new elements reinforce the view that the icon originated in Thessaloniki and its connection with this particular church, today dedicated to the Holy Apostles.
Keywords: Twelve Apostles; Thessaloniki; Palaeologan icon; epigraphy; paleographic analysis; forensic analysis